Molecular testing on bronchial washings for the diagnosis and predictive assessment of lung cancer. Issue 9 (24th June 2020) - Roncarati, Roberta; Lupini, Laura; Miotto, Elena; Saccenti, Elena; Mascetti, Susanna; Morandi, Luca; Bassi, Cristian; Rasio, Debora; Callegari, Elisa; Conti, Valentina; Rinaldi, Rosa; Lanza, Giovanni; et al.
Abstract : Cytopathological analyses of bronchial washings (BWs) collected during fibre‐optic bronchoscopy are often inconclusive for lung cancer diagnosis. To address this issue, we assessed the suitability of conducting molecular analyses on BWs, with the aim to improve the diagnosis and outcome prediction of lung cancer. The methylation status of RASSF1A, CDH1, DLC1 and PRPH was analysed in BW samples from 91 lung cancer patients and 31 controls, using a novel two‐colour droplet digital methylation‐specific PCR (ddMSP) technique. Mutations in ALK, BRAF, EGFR, ERBB2, KRAS, MAP2K1, MET, NRAS, PIK3CA, ROS1 and TP53 and gene fusions of ALK, RET and ROS1 were also investigated, using next‐generation sequencing on 73 lung cancer patients and 14 tumour‐free individuals. Our four‐gene methylation panel had significant diagnostic power, with 97% sensitivity and 74% specificity (relative risk, 7.3; odds ratio, 6.1; 95% confidence interval, 12.7–127). In contrast, gene mutation analysis had a remarkable value for predictive, but not for diagnostic, purposes. Actionable mutations in EGFR, HER2 and ROS1 as well as in other cancer genes ( KRAS, PIK3CA and TP53 ) were detected. Concordance with gene mutations uncovered in tumour biopsies was higher than 90%. In addition, bronchial‐washing analyses permitted complete patient coverage and the detection of additional actionable mutations. In conclusion, BWs are a useful material on which to perform molecular tests based on gene panels: aberrant gene methylation and mutation analyses could be performed as approaches accompanying current diagnostic and predictive assays during the initial workup phase. This study establishes the grounds for further prospective investigation. Abstract : Diagnostic and predictive assessment remains major challenges in lung cancer management. In this work, we investigate the importance of molecular investigations applied to bronchial washings collected during fibre‐optic bronchoscopy for lung lesions. Using a cancer‐specific DNA methylation panel and gene mutations analyses, we demonstrated that bronchial washing represents a useful material for performing molecular tests in lung cancer patients.